Depressive symptoms and myeloproliferative neoplasms: Understanding the confounding factor in a complex condition. (25th September 2020) - Padrnos, Leslie; Scherber, Robyn; Geyer, Holly; Langlais, Blake T.; Dueck, Amylou C.; Kosiorek, Heidi E.; Senyak, Zhenya; Clark, Matthew; Boxer, Michael; Cotter, Mary; Harrison, Claire; Stonnington, Cynthia; et al.
Abstract: Background: Philadelphia chromosome negative myeloproliferative neoplasms (MPNs), including essential thrombocythemia, polycythemia vera, and myelofibrosis, have severe function‐limiting symptom burden that is experienced by the majority of patients. Previous studies have suggested that depression may be present in over a quarter of MPN patients, but to date no studies have evaluated the relationship between depression and other variables such as symptoms. Methods: A 70‐item internet based survey regarding fatigue and mood symptoms was developed by a multidisciplinary team of MPN investigators, patients and patient advocates including Patient Health Questionnaire and the Myeloproliferative Neoplasm Symptom Assessment Form was completed by over 1300 patients with MPN diagnosis. Results: There were 309 respondents (23%) with PHQ‐2 scores ≥ 3. In this analysis, we found worse systemic symptom burden in individuals reporting depressive symptoms. Conclusion: This analysis suggests the importance of depression in contributing to as well as confounding symptomatology in MPN patients, and suggests that this critical variable should also be addressed by clinicians and researchers alike when comprehensively assessing symptom burden etiologies. Abstract : A survey of over 1300 patients with myeloproliferative neoplasms revealed 23% reported depressive symptoms and these symptoms were associated worse systemic symptom burden.